Current status and influencing factors of motor-cognitive risk syndrome in the older rural Chinese population: a cross-sectional study - Song, Jia; Yang, Teng; Liu, Luhao; Ju, Ping; Wang, Xueting; Yang, Lijuan; Leng, Minmin (Frontiers in Public Health, 2025)
ObjectiveThis study aims to screen for motor-cognitive risk syndrome (MCR) and analyze its influencing factors in rural older population in China, providing a reference for developing effective early intervention strategies.MethodsA total of 5,389 rural older adults from 33 villages in Xintai City, Shandong Province, China, were investigated using a convenience sampling method. We collected demographic information, subjective cognitive decline, gait speed, sleep quality, cognitive function, chronic pain, self-care ability, fear of falling, loneliness, nutritional status, depression, activities of daily living and social support. In this study, rural older adults were divided into an MCR group and a healthy control group. Chi-square tests, t-tests and rank sum tests were used to compare the differences in demographic characteristics between the two groups. Multivariate and linear logistic regression analyses was used to explore the factors influencing MCR in the rural older adults.ResultsA total of 3,678 rural older adults were included in this study. The prevalence rate of MCR was 11.66%. The results revealed that chronic pain, age, falls, depression, social support, living conditions, medication types, vision loss, and chronic diseases were influencing factors of MCR in rural older population (p < 0.05).ConclusionThe prevalence rate of MCR in the rural older population is 11.66%, although its associated problems are more serious. Therefore, scientific interventions should be developed for rural older population to improve their motor and cognitive function, prevent dementia, and enhance their health quality of life.